Karakteristik Pendidikan Islam bagi Anak Usia Dini (Ditinjau dalam Perspektif Pendidikan Islam) - A. Syafi' AS (MODELING: Jurnal Program Studi PGMI, 2020)
Islamic education is one of the education implemented in Islamic-based education. Islamic education is carried out at an early age to foster a sense of trust, faith and Islam in the child. With Islamic education from an early age, it shows the consistency of parents and children in determining the future and environment of children in Islam. Islamic education has characteristics in education that learns and deepens the knowledge of Islam so that it is hoped that children can develop according to the knowledge learned. The purpose of this study is to explain the characteristics of Islamic education for early childhood in terms of Islamic education perspective so that in this case children can be measured in terms of their abilities. This research method uses a qualitative study of liberty with data sources from various literature and articles. The results in this study indicate that in Islamic education for early childhood can build good basic skills in responding to and studying Islamic education for early childhood.